Blockchain Technology and its Applications in Mining Industry - Choudhury, Suryanshu (Journal of Mines, Metals and Fuels, 2022)
Blockchain technology is basically a digital ledger in the cloud which is distributed and decentralised. Blockchain is getting popularity in different industries these days because of its specific applicability features like data integrity, security, fast, transparency etc. There will not be any third party organisation intervention for control of the transactions within it. Therefore it creates interesting and vast research areas, especially from the perspective of technical challenges, expectations and limitations. These days blockchain is having wide range of applications in various industries and mining industry is no where exception to that. Many leading mining companies started implementing this technology into their operations and major application areas are fixing up smart contracts, compliance issues, addressing sustainability etc. It has got tremendous potential to fundamentally change the way the mining industry and connected supply chains operate.